; Evaluasi Penggunaan Antibiotik Pada Pasien Rawat Inap Dengan Pneumonia Di Rumah Sakit Umum Ganesha - rinandapriandini18 (Journal Pharmactive, 2025)
According to the 2018 Basic Health Research (Riset Kesehatan Dasar), theprevalence of pneumonia in Indonesia increased from 2013 by 0.4%, reaching2.0% in 2018. This indicates that pneumonia remains a significant public healthconcern. This study employed a descriptive-analytic design using a retrospectiveapproach with secondary data to evaluate the quality and quantity of antibiotic usein pneumonia patients. The qualitative aspect of antibiotic use was assessed usingthe Gyssens method, while the quantitative evaluation was conducted using theATC/DDD method. Levofloxacin was found to be the most commonly usedantibiotic, both in parenteral form (34.05 DDD/100) and oral form, indicating itsdominant role as a primary treatment option. According to the 2023 NationalClinical Practice Guidelines (PNPK), 90.26% of antibiotic use was classified asrational (Category 0) based on the Gyssens evaluation, while 9.73% fell intoCategory IVa (there was a more effective alternative available).Chi-Squareanalysis showed a p-value of 0.652 (p > 0.05), indicating that there was nostatistically significant association between the quality of antibiotic use (rationalvs. irrational) and the length of hospital stay (?3 days vs. >3 days).Although thestatistical analysis did not yield a significant result, irrational use of antibiotics stillposes risks such as reduced treatment effectiveness, increased antimicrobialresistance, prolonged hospitalization, higher treatment costs, and potential clinicalcomplications. Therefore, rational antibiotic use remains essential to supporttreatment success and prevent adverse long-term outcomes.